Complete F-type mitochondrial genome of Chinese freshwater mussel Lamprotula tortuosa. (October 2013) - Wang, Guiling; Cao, Xinrong; Li, Jiale
<x xml:space="preserve">Abstract</x> Lamprotula tortuosa is the endemic species of freshwater pearl mussel in China. The complete F-type mitochondrial genome of L. tortuosa was first determined. This circle genome (15, 722 bp in size) comprises 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, except for COI, CYTB, ND6, and ND4L, with TTG, ATT, ATT, and ATA start codon, respectively; the remaining protein-coding genes initiated with the orthodox ATG start codon. There were 25 noncoding regions found throughout the mitogenome of L. tortuosa, ranging in size from 1 to 241 bp, the largest of which is between ND5 and tRNAGln (241 bp), but is shorter than the control region sequences(about 280 bp) of freshwater mussels from Poland and South Korea.